Supporting a patient with learning disabilities through screening and treatment for primary breast cancer. (15th December 2022) - Cooper, Deborah
Abstract : This article presents a case study evaluation of supporting a patient with learning disabilities through the NHS Breast Screening Programme diagnostic pathway and subsequent treatments for breast cancer. The process encompassed best interests meetings and treatment planning, surgeries, chemotherapy and anti-Her2 treatments, radiotherapy and endocrine therapy. Problems that occurred during this period included issues around completing surgery, managing chemotherapy treatment during the COVID-19 pandemic and the feasibility and tolerance of radiotherapy. The role of a breast care nurse in this patient's pathway was to facilitate treatment, support the patient and her family, and to liaise with the wider nursing and medical teams to coordinate care.